ONLINE LEARNING CLASSROOM MANAGEMENT DURING THE COVID-19 PERIOD AT PGMI IAIN BATUSANGKAR - Yufi Latmini Lasari (STKIP Pesisir Selatan, 2021)
This research was motivated by the Covid-19 pandemic which was designated a national epidemic sothat it began in mid-March 2020 the face-to-face lecture process between lecturers and students canno longer be carried out normally as usual. To respond to this, the lecturers of PGMI IAINBatusangkar carry out online lecture activities. Based on these facts, this research was conductedwith the aim of describing the forms of classroom management carried out by lecturers in onlinelearning during the Covid-19 period at PGMI IAIN Batusangkar. The research method used in thisresearch is descriptive qualitative method. The results illustrate that there are several stages carriedout by researchers in managing online learning classes at PGMI IAIN Batusangkar, namely: 1) theplanning stage, 2) the implementation stage, and 3) the control stage